2010
DOI: 10.1111/j.1745-4565.2009.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Aflatoxins in Pistachio Nuts in Esfahan Province of Iran

Abstract: Aflatoxins (AFs) are highly toxic and carcinogenic secondary fungal metabolites and have been detected in various food commodities including pistachio nuts. One hundred samples of pistachio nuts, purchased from retail shops and local markets in Esfahan province of Iran from September to November 2007, were analyzed for AFs content by immunoaffinity column (IAC) cleanup with liquid chromatography and fluorescence detection. Results showed that the frequency of total AFs (AFT), aflatoxin B1 (AFB1), aflatoxin B2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…According to Cheraghali and others (2007), 11.8% and 7.5% of 10068 Iran pistachio nut samples were above the maximum tolerated level (MTL) of AFB1 and total aflatoxins, respectively. In another study from Iran, Pour and others (2010) reported 36% and 29% of pistachio nuts had exceeded maximum tolerable limit (5 and 15 μg/kg) set for AFB1 and total aflatoxins by European Union.…”
Section: Resultsmentioning
confidence: 93%
“…According to Cheraghali and others (2007), 11.8% and 7.5% of 10068 Iran pistachio nut samples were above the maximum tolerated level (MTL) of AFB1 and total aflatoxins, respectively. In another study from Iran, Pour and others (2010) reported 36% and 29% of pistachio nuts had exceeded maximum tolerable limit (5 and 15 μg/kg) set for AFB1 and total aflatoxins by European Union.…”
Section: Resultsmentioning
confidence: 93%
“…Fungal deterioration of stored products is a chronic problem worldwide, aggravated in warm and humid regions, ideal for aspergilli and aflatoxin production (Pour et al 2010). Toxic synthetic compounds are presently used to manage these fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The fungal growth can be minimized by adopting the effective drying tools and proper storage operations for crops (Rachaputi, Krosch, & Wright, 2002). The uncontrolled storage conditions have lead to aflatoxin contamination in pistachio nuts (Pour et al, 2010). The AFs levels in dry fruits and nuts are lowered which have been stored in shells as compared to those stored without shells (Iqbal et al, 2018).…”
Section: Control Methods For Aflatoxinsmentioning
confidence: 99%
“…They are produced in animal feeds and various food commodities (e.g., peanuts, maize grains, cereals, etc.) by the fungal strains (mainly by Aspergillus parasiticus and Aspergillus flavus ; rarely by Euderces venezuelensis, Emericella astellata, Aspergillus tamarii, Aspergillus pseudotamari, Aspergillus ochraceoroseus and Aspergillus bombycis ) (Bennett, Kale, & Yu, ; Pour, Rasti, Zighamian, & Garmakhani, ). They were first known in 1960s in United Kingdom, where more than 100 thousand Turkey poultry birds suffered from death by ground nut meal infected with A. flavus (Kumar, ).…”
Section: Introductionmentioning
confidence: 99%